Labour legislation and market economy: are they compatible terms? - Balta Varillas, José (Universidad del Pacífico, 1991)
While it is certainly true that some modifications still need to be made in order to adapt Peruvian Labor Law to the social and economic needs of the country, it cannot be douted that some positive steps forward have been taken recently in that direction. Our constitutional regulations are flexible enough to allow such modifications, even though they might imply a change in the very structure of certain labor rights. This is proved not only by the recent legislation modifications to severance pay and collective bargaining, but also by a distinct constitutional possibility of modifying substantially the present work stability system.